(untitled) (Al-Academy, 2026)
Cinema is one of the most important social documents that contribute to shaping the dynamic laws of societies, and leads to understanding the nature of the relationship between man and society. The film reveals phenomena face to face between the subject and the recipient, and presents topics from lived reality, and this comes from the relationship between the art of cinema and sociology. Cinema has great potential in dealing with topics - social phenomena - that express people’s interests and needs, as an important social expression, and it also conveys reality to them in a simplified way, as cinema is a result of arts and sciences, with its elements of sound and image, sociology, politics, psychology, etc.; hence, the researcher defined the title of his research topic as (directorial treatments of social phenomena in Korean cinema). The research came in five chapters, as the first chapter was a methodological framework that included the research problem, which was formulated with the following question: (What is the directorial treatment of social phenomena in Korean cinema?), then the importance of the research and the need for it, as the research goal was determined in (revealing the directorial treatment of social phenomena in Korean cinema), as for the second chapter (the theoretical framework and previous studies), it included three topics: the first topic is cinema and society, the second topic is social phenomena, and the third topic is the directorial treatment of social phenomena, after which the researcher reached several indicators and adopted them as tools for analyzing the sample, and the third chapter included the research procedures, including the research methodology, which is the descriptive methodology, the research community, and the research sample represented in the movie (Parasite). As for the fourth chapter, the sample was analyzed, and finally the fifth chapter, in which the results, conclusions, recommendations and suggestions were presented, and the research was concluded with sources and a summary in English